Dampak Penggunaan Pupuk Organik Dan Anorganik Pada Tanaman Kedelai (Glycine Max) - Hepi Kardiani Mendrofa; Octavianis Laoli; Lentri prisskila Waruwu; Joy Blesswan Endriyanti Mendrofa; Manyupril Lutkevin Fatlow Zai; Asdian Julianti Dawolo; Yoel Melsaro Larosa; Putra Hidayat Telaumbanua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Fertilization is a crucial aspect in increasing the productivity of soybean (Glycine max L.), both in terms of vegetative growth and yield. Organic fertilizers, such as compost and manure, play a long-term role in improving the physical, chemical, and biological structure of the soil, increasing microbial activity, and gradually supporting nutrient availability (Widodo et al., 2018; Yang et al., 2004). Meanwhile, inorganic fertilizers such as urea, NPK, and SP-36 provide nutrients quickly and efficiently, thereby accelerating plant growth and increasing yields in a relatively short time (Putra Manik et al., 2019). However, excessive use of inorganic fertilizers can lead to decreased soil fertility and environmental pollution (Nugroho et al., 2017). Several studies indicate that the combination of organic and inorganic fertilization can create synergy that increases nutrient uptake efficiency, improves soil quality, and supports sustainable plant productivity (Migunansyah, 2009; Khaerunisa, 2013). Therefore, an integrated fertilization strategy is highly recommended in an environmentally friendly soybean cultivation system.